Effect of irrigation on soil water depletion, vegetative growth, yield and berry composition of the grapevine variety Touriga Nacional - Gouveia,João (2012)
Aiming to assess the effects of irrigation amount on vegetative growth, yield and berry composition of the red variety Touriga Nacional (Vitis vinifera L.) a field trial was installed at the Centro de Estudos Vitivinícolas do Dão, Nelas, Portugal. The effects of three irrigation treatments (DI30 - 30% of ETc; DI50 - 50% ETc and FI - 100% ETc) were compared to a control non-irrigated (NI) during three growing seasons (2006-2008). Irrigation affected significantly the fraction of available soil water and the pattern of soil water extraction by the roots either in the row and interrow. Predawn leaf water potential was also influenced by irrigation amount being the main differences observed between FI (highest values) and NI (lowest values). Compared to NI, the full irrigation treatment (FI) induced a significantly higher vigour while the deficit irrigation treatments (DI30 & DI50) returned intermediate values. The FI treatment induced a significantly higher yield as compared to the other treatments which returned similar values. Compared to the control non-irrigated, the deficit irrigation treatments presented similar berry composition during all the three seasons while the FI treatment showed a significantly higher total acidity, lower total soluble solids and anthocyanins concentration. With the exception of the higher yield observed in FI treatment, in these three seasons irrigation had no other agronomical advantages enabling us to conclude that, in the ecological and viticultural conditions of the experiment, irrigation seems not to be necessary. However, further studies are needed mainly in soils with lower water holding capacity and in dryer years which frequency are expected to increase in the near future as a consequence of the climate change.